Tufts Lacrosse Team Practice Session (Tufts Archival Research Center, 2006)
The orginal print is not located in the DCA. 5 x 7, Left to Right : Tim Ring (c), Ray Thompson, Bob Eccles, Bob Kraft, Len Brown, Waine MacArdle, Fred Davis